Analysis of Vendor Trucking Management Factors, Delivery Timeliness, and Fleet Availability on IKEA Export Goods Delivery at PT XYZ Logistics Jakarta - Chairunnisa Chairunnisa; Siti Maemunah; M Kadarisman (Dinasti Review, 2026)
This study aims to analyze the effect of vendor trucking management, delivery timeliness, and fleet availability on export delivery performance at PT XYZ Logistics Jakarta. A quantitative research approach was employed, utilizing hypothesis testing to examine the relationships among these variables. Data collection was conducted using a structured questionnaire with a five-point Likert scale, involving logistics personnel engaged in freight forwarding activities for IKEA. The collected data was analyzed using the Partial Least Squares Structural Equation Model (PLS-SEM). The results indicate that vendor trucking management has a positive effect on delivery timeliness. Fleet availability significantly influences export delivery performance. Additionally, delivery timeliness positively impacts export efficiency. The findings also reveal that vendor trucking management indirectly affects export delivery performance through its influence on delivery timeliness. Moreover, fleet availability moderates the relationship between vendor management and delivery success. The study suggests that logistics firms should prioritize vendor accountability, adopt AI-driven scheduling analytics, and invest in fleet modernization to enhance operational resilience and shipment accuracy.